2021
DOI: 10.3389/fphar.2021.685518
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Polypharmacy, Hyperpolypharmacy and Potentially Inappropriate Medication Use in Older Adults in India: A Systematic Review and Meta-Analysis

Abstract: Background: Older people often receive multiple medications for chronic conditions, which often result in polypharmacy (concomitant use of 5‒9 medicines) and hyperpolypharmacy (concomitant use of ≥10 medicines). A limited number of studies have been performed to evaluate the prevalence of polypharmacy, hyperpolypharmacy, and potentially inappropriate medication (PIM) use in older people of developing countries. The present study aimed to investigate regional variations in the prevalence of polypharmacy, hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 62 publications
2
38
3
2
Order By: Relevance
“…Furthermore, polypharmacy is more frequently observed in inpatients (73%) than outpatients (23%). This is different from another study about the prevalence of polypharmacy observed in two categories ( Bhagavathula et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, polypharmacy is more frequently observed in inpatients (73%) than outpatients (23%). This is different from another study about the prevalence of polypharmacy observed in two categories ( Bhagavathula et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…A patient who takes between 5 and 9 different drugs per day is said to have polypharmacy and a patient who takes 10 or more drugs per day is said to have hyper-polypharmacy. 83,84…”
Section: Platinum Drug–drug Interactions With Non-cancer Medicinesmentioning
confidence: 99%
“…A patient who takes between 5 and 9 different drugs per day is said to have polypharmacy and a patient who takes 10 or more drugs per day is said to have hyper-polypharmacy. 83,84 This is an issue for chemotherapy, and especially for platinum-based chemotherapy, given that 46% of hospital chemotherapy patients are administered a platinum, 8 and because 35% of elderly (70+ years of age) cancer patients have polypharmacy. 85 Because of this, 30-75% of these patients are likely to experience changes in efficacy and side effects due to drug-drug interactions with their platinum agents.…”
Section: Platinum Drug-drug Interactions With Non-cancer Medicinesmentioning
confidence: 99%
“…Cabe aclarar que el término polifarmacia tiene más de 24 definiciones en la literatura médica y que se considera como una prescripción extraordinaria, es decir, cuando una persona toma más medicamentos de los necesarios o tiene una prescripción inadecuada, con puntos de corte que varían desde 4 hasta 10 o más; cuando se sobrepasan los nueve medicamentos algunos autores lo denominan hiperpolifarmacia (21,22). Para este estudio se consideró polifarmacia el consumo de 4 medicamentos o más, lo que podría llevar a limitaciones en la comparación con investigaciones que utilizaron otros puntos para definirla.…”
Section: Discussionunclassified